2008
DOI: 10.1002/ana.21436
|View full text |Cite
|
Sign up to set email alerts
|

Gray matter atrophy in multiple sclerosis: A longitudinal study

Abstract: Gray matter tissue damage dominates the pathological process as MS progresses, and underlies neurological disabillity. Imaging correlates of gray matter atrophy indicate that mechanisms differ in RRMS and SPMS. These findings demonstrate the clinical relevance of gray matter atrophy in MS, and underscore the need to understand its causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
526
14
17

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 621 publications
(588 citation statements)
references
References 39 publications
31
526
14
17
Order By: Relevance
“…32 Over the past few years, several studies have used MRI derived methods to assess brain volume changes, revealing that atrophy can be present even in the early stages of MS, and that it advances over the disease course (Figure 2). 33,34 Generally speaking, brain volume changes can be an important measure of tissue damage in patients with MS. 32 Indeed, baseline atrophy and high rates of subsequent volume loss are associated with cognitive impairment, fatigue and disability progression over the long term. 32,[35][36][37][38][39][40][41] In a complex disease such as MS, brain volume loss results from the sum of and interactions between various destructive pathological processes, 42 including irrever sible demyelination, and axonal and/or neuronal loss.…”
Section: Focal Lesionsmentioning
confidence: 99%
“…32 Over the past few years, several studies have used MRI derived methods to assess brain volume changes, revealing that atrophy can be present even in the early stages of MS, and that it advances over the disease course (Figure 2). 33,34 Generally speaking, brain volume changes can be an important measure of tissue damage in patients with MS. 32 Indeed, baseline atrophy and high rates of subsequent volume loss are associated with cognitive impairment, fatigue and disability progression over the long term. 32,[35][36][37][38][39][40][41] In a complex disease such as MS, brain volume loss results from the sum of and interactions between various destructive pathological processes, 42 including irrever sible demyelination, and axonal and/or neuronal loss.…”
Section: Focal Lesionsmentioning
confidence: 99%
“…Our findings suggest, therefore, that future studies should concentrate more on understanding the pathogenetic mechanisms leading to selective SDGM rather than to cortical GM damage in patients with early RRMS. Central atrophy development in early RRMS (10% larger NLVV than that in patients with CIS) emphasizes the need for better understanding of pathogenetic mechanisms leading to selective central and SDGM atrophy.The disparate findings of GM atrophy in patients with CIS between different studies [7][8][9]11,14,16,21 point to the heterogeneity of the disease in patients with CIS and the inclusion criteria for the studies in which they are enrolled. A recent study revealed significant global GM volumetric differences in contrast to our own between patients with CIS and RRMS 16 ; however, patients with CIS did not have to fulfill the oligoclonal bands criterion.…”
mentioning
confidence: 99%
“…Brain atrophy during RRMS is highly relevant, however, as it has been shown to predict future ambulatory 13 and cognitive 9 disability. Accelerated gray matter atrophy occurs in patients at all stages of MS as well 14 and correlates better with disability than other MRI measures. 11 The picture emerges of a disease that is pathologically active from onset, in which CNS tissue may be damaged or destroyed without obvious clinical manifestations during early disease stages.…”
Section: Irreversible Axon and Myelin Injury Occurs Early In The Courmentioning
confidence: 93%